1998
DOI: 10.1055/s-2007-1000173
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Upper‐Extremity Peripheral‐Nerve Injuries with ePTFE Conduits

Abstract: This reported investigation was designed to determine the role of a new synthetic conduit-expanded polytetrafluoroethylene (ePTFE) tube--in clinical repair of median and ulnar nerves in the upper extremities. The main goals of this study were: to determine the effectiveness of the ePTFE conduit in clinical nerve reconstruction; to evaluate the potential of this technique in reconstruction of various nerve gaps (1.5 to 6 cm); and to analyze the results of repair with the ePTFE tube regarding different mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 6 publications
(9 reference statements)
1
37
0
6
Order By: Relevance
“…The original idea was to provide support, structure to guide axonal regrowth and form a stable barrier against connective tissue infiltration [73,100,101]. Synthetic nerve conduits made of ePTFE were successfully applied in a 4-cm nerve gap, in human [102]. Second-generation nerve conduits are resorbable, biocompatible tubes and are FDA approved and commercially available through different materials.…”
Section: Manufactured Conduitsmentioning
confidence: 99%
“…The original idea was to provide support, structure to guide axonal regrowth and form a stable barrier against connective tissue infiltration [73,100,101]. Synthetic nerve conduits made of ePTFE were successfully applied in a 4-cm nerve gap, in human [102]. Second-generation nerve conduits are resorbable, biocompatible tubes and are FDA approved and commercially available through different materials.…”
Section: Manufactured Conduitsmentioning
confidence: 99%
“…Testing the diameter and thickness of these conduits found that increasing one or both of these parameters resulted in reduced functional recovery for the patient [44]. Furthermore, neither silicone nor PTFE showed potential in nerve regeneration in gaps larger than 4 cm in human studies [89]. Interestingly however, silicone conduits with small punctures produced improved regeneration on rat sciatic nerves compared to solid silicone conduits [24].…”
Section: Conduitsmentioning
confidence: 99%
“…One must avoid tension at the repair site, at all costs. Small nerve gaps can be resolved by mobilizing the nerve ends, through proximal nerve transpositions, or by using bridging veins, nerve conduits, silicone and absorbable tubes [47][48][49]. Although the epineural microsurgical suture is mostly performed, there is also the proposition for microsurgical interfascicular nerve grafting when there are larger gaps [50].…”
Section: Treatmentmentioning
confidence: 99%